2019
DOI: 10.3390/toxins11100606
|View full text |Cite
|
Sign up to set email alerts
|

The Mode of Action of Bacillus Species against Fusarium graminearum, Tools for Investigation, and Future Prospects

Abstract: Fusarium graminearum is a pervasive plant pathogenic fungal species. Biological control agents employ various strategies to weaken their targets, as shown by Bacillus species, which adopt various mechanisms, including the production of bioactive compounds, to inhibit the growth of F. graminearum. Various efforts to uncover the antagonistic mechanisms of Bacillus against F. graminearum have been undertaken and have yielded a plethora of data available in the current literature. This perspective article attempts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 116 publications
2
42
0
1
Order By: Relevance
“…Streptomyces is a broad and highly potent inhibitory phenotype that might be competitive 'hot spots' to inhibited rice rhizosphere (Schlatter and Kinkel, 2014;Behie et al, 2017). Ntushelo et al (2019) stated that Bacillus sp. showed insignificant antagonistic activity against F. graminearum and this bacterium has potential use for Bio-agriculture to supplement the despised control measures.…”
Section: Effect Of Bacterial Isolates Against P Infestans In Detachementioning
confidence: 99%
“…Streptomyces is a broad and highly potent inhibitory phenotype that might be competitive 'hot spots' to inhibited rice rhizosphere (Schlatter and Kinkel, 2014;Behie et al, 2017). Ntushelo et al (2019) stated that Bacillus sp. showed insignificant antagonistic activity against F. graminearum and this bacterium has potential use for Bio-agriculture to supplement the despised control measures.…”
Section: Effect Of Bacterial Isolates Against P Infestans In Detachementioning
confidence: 99%
“…siderophores) and lytic enzymes (i.e. chitosanases, glucanases, cellulases, proteases, chitinases) able to directly alter pathogen fitness and aggressiveness [40,47,155].…”
Section: Additional Genes Encoding For An Extensive Range Of Beneficimentioning
confidence: 99%
“…Finally, B. subtilis may produce an extensive range of antimicrobial molecules, chelators and lytic enzymes to alter pathogen fitness and aggressiveness [40][41][42][43][44]. According to literature, these beneficial molecules include ribosomally synthesized antimicrobial peptides (RP, including the posttranslationally modified peptides RiPP), non-ribosomally synthesized peptides (NRP), polyketides (PK), as well as other uncommon antimicrobial volatile compounds (the inorganic and organic ViCs and VOCs, respectively) and other terpenoid secondary metabolites as listed in Table 1 [13,[40][41][42][43][44][45][46][47][48].…”
mentioning
confidence: 99%
“…Globally, biotic stresses such as pests and pathogens are main factors of threat for the production of crops and a recently study reported that crop loss about 8-40% worldwide is due to fungal pathogens. 1 Among these plant diseases, the most important economic pathogen is Fusarium species, which cause a wide range of diseases including wilts, head blights, fruit rots, and root rots. The population of disease caused by Fusarium graminearum was reported in the Netherlands, western Canada, Great Britain, Germany, northwest Europe and North America.…”
Section: Introductionmentioning
confidence: 99%